2013
DOI: 10.1111/iwj.12172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic wounds and structural quality indicators of chronic wound care in Dutch nursing homes

Abstract: The aim of this study was to measure the prevalence of (infected) chronic wounds in Dutch nursing homes and to explore which signs and symptoms are used to diagnose infected chronic wounds. Moreover, it was to determine which structural quality indicators related to chronic wound care at ward and institutional levels were fulfilled. In April 2012, as part of the annual National Prevalence Measurement of Care Problems of Maastricht University [Landelijke Prevalentiemeting Zorgproblemen (LPZ)], a multi-center cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 22 publications
(23 reference statements)
0
37
0
Order By: Relevance
“…However, no attempts were made to differentiate clinical signs of infection between different types of chronic wounds. When these criteria were used to diagnose infection in 192 patients with 211 chronic wounds from a Dutch nursing home, Rondas et al found that pain, increased exudate, erythema, and delayed healing were the only relevant signs to diagnose infected chronic wounds . More importantly, no association between clinical signs of infection and microbiological cultures, taken by a Levine‐technique swab, was found.…”
Section: Resultsmentioning
confidence: 99%
“…However, no attempts were made to differentiate clinical signs of infection between different types of chronic wounds. When these criteria were used to diagnose infection in 192 patients with 211 chronic wounds from a Dutch nursing home, Rondas et al found that pain, increased exudate, erythema, and delayed healing were the only relevant signs to diagnose infected chronic wounds . More importantly, no association between clinical signs of infection and microbiological cultures, taken by a Levine‐technique swab, was found.…”
Section: Resultsmentioning
confidence: 99%
“…In a cross‐sectional study of 77 chronic leg ulcers from 75 participants, De Souza found 27% of the ulcers were infected . Similarly, Rondas et al in 2015 found 22% (16/72 chronic wounds) were found infected . This discrepancy could be explained by the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the 2014 study, the sample (77 cases) was much smaller than the current study sample (561 cases). Second, in the 2015 study, the majority of the chronic wounds were pressure ulcers (46%) and post‐surgical wounds (9.5%), while venous leg ulcers were only 3.6% and arterial ulcers 1.6% . Importantly, this prevalence was still significant generating a number of infected ulcers in the whole population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, the chronic wound burden lies chiefly within the elderly population [6,11,12] and the morbidity accompanying age-related delay in healing, is readily acknowledged [11,12]. In 2013 in the Netherlands, a multi-centre cross-sectional point-prevalence measurement on chronic wounds in nursing home patients was conducted [13]. Out of 1514 patients, 63 patients had one or more chronic wounds, which resulted in a prevalence of 4.2%.…”
Section: Introductionmentioning
confidence: 99%